Kontroversi Masyarakat Mengenai Undang-Undang Cipta Kerja (Omnibus Law) (International Forum of Researchers and Lecturers, 2024)
The purpose of writing this journal is to find out more deeply how the public responds to the passing of the Job Creation Law. The method used is descriptive qualitative by explaining and describing existing conditions. Data collection techniques use literature studies by collecting secondary data taken from journals or previous research. The result of the discussion is that there are many people who do not agree with it because they consider that there are several articles that are problematic and controversial. The pro party is the government because this Omnibus Law exists because of the complexity that arises, namely about kining, taxation, land acquisition and other aspects related to investment.